A Systematic Literature Review on the Impact of Reading Literacy on Students’ Critical Thinking Skills in Vocational Education - Nurtanto, Muhammad; Nawanksari, Septiari

(untitled) - Sutrisno, Valiant Lukad Perdana; Majid, Nur Wachid Abdul; Kholifah, Nur (Journal of Teaching and Learning)

(untitled) (University of Windsor, 2026)
This study is a systematic literature review (SLR) aimed at identifying and analyzing the relationship between reading literacy and critical thinking skills among vocational school pupils. Following the PRISMA guidelines, a total of 20 selected articles published between 2015 and 2025 were thoroughly reviewed using databases such as Scopus, ERIC, Web of Science, and Google Scholar. The findings indicate that reading literacy serves not only as a tool for text comprehension but also as a fundamental component in fostering pupils' analytical, reflective, and evaluative thinking abilities. Instructional strategies such as reciprocal teaching, problem-based learning, and critical questioning have been proven effective in simultaneously enhancing both reading literacy and critical thinking skills. Moreover, digital literacy plays a crucial role in fostering critical thinking in the age of information. Nevertheless, the study identifies several limitations, including inconsistencies in measurement methods and the underrepresentation of studies from developing countries. The results highlight the importance of integrating reading literacy and critical thinking into the vocational education curriculum, as well as the need for strengthened policy support, teacher training, and the development of valid and context-sensitive assessment instruments.